First simplify any expressions inside parentheses:
- (
72
÷
8
)
−
2
×
3
+
1
= 9 - 6 + 1 = 4
- 72
÷
(
8
−
2
)
×
3
+
1
= 12 × 3 + 1 = 37
- 72
÷
(
8
−
2
)
×
(
3
+
1
)
= 12 × 4 = 48
- 72
÷
8
−
2
×
(
3
+
1
)
= 9 - 8 = 1
Now we can order them from least to greatest:
1. 72÷(8−2)×(3+1) = 48
2. 72÷(8−2)×3+1 = 37
3. (72÷8)−2×(3+1)+1 = 4
4. 72÷8−2×(3+1) = 1
Therefore, the order from least to greatest is:
1. 72÷(8−2)×(3+1) = 48
2. 72÷(8−2)×3+1 = 37
3. (72÷8)−2×(3+1)+1 = 4
4. 72÷8−2×(3+1) = 1
Arrange the expressions below in order from least to greatest. Place the least at the top and greatest at the bottom.
(
72
÷
8
)
−
2
×
3
+
1
72
÷
(
8
−
2
)
×
3
+
1
72
÷
(
8
−
2
)
×
(
3
+
1
)
72
÷
8
−
2
×
(
3
+
1
)
1 answer